Ceftaroline: a cephalosporin with expanded Gram-positive activity. (February 2009) - Kanafani, Zeina A; Corey, G Ralph
Infections caused by resistant Gram-positive pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) are now posing a major health risk for patients in hospital and community settings. There is a need to evaluate new antibiotics that would offer reliable clinical efficacy combined with a favorable safety profile for the treatment of such infections. Ceftaroline is a new member of the cephalosporin class of antibiotics with expanded activity against Gram-positive pathogens such as MRSA, vancomycin-intermediate S. aureus, vancomycin-resistant S. aureus and multidrug-resistant Streptococcus pneumoniae, while retaining good activity against common Gram-negative organisms. Phase II and III studies have shown ceftaroline to be an effective and well-tolerated treatment for complicated skin and skin-structure infections compared with standard therapy. Trials are ongoing in the treatment of community-acquired pneumonia.